From test tube to Turner – the role of the chemist in art. (1st December 2013) - Abbott, Andrew
Most modern art galleries arrange their collections in chronological order and to the average viewer it often the changes in style, fashion or subject matter that is indicative of the passage of time. Far less noted, although possibly more obvious is the change in paint which occurred. Ultimately it is the evolution of chemical techniques that is responsible for these developments. In this article, the major changes in chemical techniques and elemental discovery will be mapped onto the subsequent development of pigments and their use in artworks.